Institutional Effectiveness and Inclusions: Public Perceptions on Indonesias Disaster Management Authorities - Tanesab, Janiscus Pieter (TDMRC, Universitas Syiah Kuala, 2020)
Disaster risk events always have impacts on disaster losses in terms of the sustainability. The phenomena of natural hazards continue to threaten the social and economic livelihoods of the community, while policies and stipulated regulations for mitigating disaster risks reduction (DRR) endlessly become polemics both in national and local government institutions. The study was conducted to address public perceptions on the effectiveness of Indonesias Disaster Management Authorities in managing DRR across the archipelago. Relying on the coproduction principle, the author conducted a case-study through in-depth interviews and literature studies to gain public insights, including related encountered situations revealing perceptions on the track-records of the performance of disaster management authorities in a SWOT analysis. The results indicated that both national and local disaster management authorities respectively are less effective due to the lack of effective communication, coordination, collaboration, and synchronization in managing DRR. Moreover, the scarcity of existing potential leaderships for decision makings through vertical and horizontal negotiations, and lack of persuasive approaches for communities engagement at all risk cycles. The study highlighted the importance of reforming the status of national disaster management authority thus, it is more powerful in functioning to command, monitor, and control the lower disaster risk institutions and be able to synergize implemented policies with other government institutions. The study also suggested increasing coproduction through public-private partnerships and philanthropies to upgrade innovations, education and training, also psychological healings as a recovery process for greater sustainable development.